The population structure of two estuarine fish species, atherina breviceps (Pisces: Atherinidae) and gilchristella aestuaria (Pisces: Clupeidae), along the Southern African coastline - Norton, Olivia Bridget (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
Phylogeographic patterns of coastal organisms with different life histories and breeding strategies may reveal patterns not consistent with the current delineation of the biogeographic provinces around South Africa. The subdivision of the South African coastline into these three main climatological or biogeographic regions: namely the cool temperate west coast, the warm temperate south coast and the subtropical east coast, is based on average seawater temperatures and hydrological conditions. Genealogies of two estuarine fish species Atherina breviceps, a marine breeder, and Gilchristella aestuaria, an estuarine spawner, were reconstructed using mitochondrial DNA (mtDNA) control region sequences. The study comprised two components, an assessment of a small dataset of both fish species to compare their population structure along the South African coastline and a more comprehensive investigation of the phylogeography of G. aestuaria collected from 21 estuaries around the coast. The comparative study of A. breviceps and G. aestuaria indicate different population distribution patterns along the South African coastline. Results of the A. breviceps analysis demonstrate substantial gene flow due to the random mixing of alleles, while the comparative G. aestuaria dataset indicates a more structured population and considerably less gene flow. The G. aestuaria population demonstrates geographic separation into four groups, namely the west coast (Great Berg), Bot (south coast), Seekoei (south coast) and east coast (Bushmans, Kasouga and Cefane). Results from the larger G. aestuaria dataset indicate that the phylogeographic patterns observed during this study do not conform to existing biogeographic boundaries along the southern African coastline. The delineation identified during this study between the warm temperate and subtropical regions is further south than originally perceived and this southward extension can be ascribed to the prevailing hydrology. The life history patterns and ecology of these two estuarine fish species appears key to understanding their population structure. These factors interact with environmental characteristics such as physical oceanography and the distribution of estuaries (along the coastline) to explain the observed distribution patterns and population structure of A. breviceps and G. aestuaria.
Keywords: Estuarine fishes -- South Africa; Estuarine ecology -- South Africa; Clupeidae -- South Africa; Silversides -- South Africa